Causes for Lack of Usage of Satefy Harness Among Construction Workers in Malaysia: An Investigation - HASMORI, MUHAMMAD FIKRI; Nur Asmidar FarhanimMohd Akhir,; Ilias Said, (Recent Trends in Civil Engineering and Built Environment, 2020)
Most of the construction workers in Malaysia does not use a safety harness when working at height is, even the workers are constantly exposed to fall hazard and the use of safety harnesses is required by law such as OSHA 1994. Based on Surry's model, the main reason for the workers not using safety harnesses is identified as their personal decisions and behaviour not to do so. The objectives of this research are to investigate the causes for lack of usage of safety harness among construction workers using Theory of Planned Behaviour (TPB) and to suggest control measures to encourage construction workers for using a safety harness. A structured questionnaire was constructed according to the objectives that consist of four parts was used for data collection and the respondents were comprised of construction workers in construction sites at the southern part of Peninsular Malaysia which is Johor. The causes for the lack of usage of safety harness among construction workers were explored through theoretical analysis and empirical test. The methods that have been used to analyze the data were descriptive statistic and inferential statistic. As much as 86 construction workers from different sites in Johor completed the questionnaires developed based on TPB. Theory of Planned Behaviour shows that there are 28.5% changes in behaviour due to the changes in the intention of construction workers. The empirical test shows that the discomfort of using safety harness, the employer does not provide the safety harness, negative pressures from gangmasters, foreman and safety officers and lack of knowledge about how to use safety harness are the main causes of construction workers not using safety harness. According to the results of the empirical tests, 13 out of 14 construction workers suggested that the control measures to encourage the use of safety harnesses among construction workers is to provide more safety training.